2009
DOI: 10.1016/j.desal.2008.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical water quality in Ghana: Prospects for water supply technology implementation

Abstract: During an extensive sampling trial in Ghana, a number of physico-chemical water quality problems have been identified. For example, pH values of the collected samples ranged from 3.69 to 8.88, while conductivity ranged from 10 to 45000 µS/cm and turbidity from 0 to > 542 NTU. Many water samples analysed breached the drinking water quality guidelines. High levels of heavy metals were found and also locations high in sulphate and nitrate. In some regions chemical contaminants such as fluoride occur naturally and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…On the contrary, groundwater pH at location GW3 during the dry season is below the WHO limit suggesting possible acidity. Schafer et al (2009) and Ayantobo et al (2013) in previous studies reported that low pH in groundwater may be due to natural geochemical and biochemical processes within the aquifers. The GW3 sampling point is within the mining and processing facilities, it is thus possible that seepage of effluent discharges, as well as surface and agricultural run-off may contribute to the increased concentration of ions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the contrary, groundwater pH at location GW3 during the dry season is below the WHO limit suggesting possible acidity. Schafer et al (2009) and Ayantobo et al (2013) in previous studies reported that low pH in groundwater may be due to natural geochemical and biochemical processes within the aquifers. The GW3 sampling point is within the mining and processing facilities, it is thus possible that seepage of effluent discharges, as well as surface and agricultural run-off may contribute to the increased concentration of ions.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and potassium are not a health concern and are not regulated (Schafer et al, 2009). Although, the reported values may not implicate the public health, however, the presence of multivalent cations such as Ca may pose negative treatment's implications for certain processes (Schafer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, policies are often designed to tackle water supply and sanitation situations simultaneously. This is evident when the Government of Ghana implemented a policy in 1993 aimed to ensure the sustainability of water and sanitation facilities provided through a demand responsive approach (Schäfer et al, 2009). …”
Section: Sanitation In the Bolgatanga Municipalitymentioning
confidence: 99%